Force-dependent structural dynamics of the giant nesprin-2 - Fei Shang; Yuhang Zhang; Jiaqing Ye; Zhuwei Zhang; Xingyu Qi; Hu Chen; Miao Yu; Shimin Le (Proceedings of the National Academy of Sciences, 2026)
The nesprin protein family serves as a critical physical bridge between the cytoskeleton–a fundamental structural scaffold and mechanotransduction hub of the cell, and the nucleus–an intriguing and emerging mechanoresponsive element. Due to the external mechanical cues and the nucleo-cytoskeletal dynamics, the nesprins are physiologically under forces. However, the dynamics of nesprins within physiological forces and loading rates remain largely unexplored. In this study, we employ magnetic-tweezers-based single-molecule manipulation alongside molecular dynamic simulations and AlphaFold structural predictions to comprehensively investigate the dynamics of force-bearing spectrin repeat (SR) domains of the giant nesprin-2 protein. Through direct quantification, we unveil that the numerous SRs undergo mechanical unfolding and refolding dynamics with distinct transition rates within several pN scale. Furthermore, we show that the giant nesprin-2 could act as an effective molecular absorber adeptly maintaining forces on the nucleoskeleton and cytoskeleton linkage within a few pN across displacement spans exceeding one μm. Notably, our findings imply that subtle pN-level mechanical forces intricately modulate nesprin–protein interactions via the dynamics of domain folding and unfolding. Collectively, our study offers a comprehensive understanding of the mechanical characteristics of nesprin-2 giant, shedding light on its pivotal role in nucleoskeleton–cytoskeleton mechanotransduction.